Adsorption of the 2,2-Dichlorovinylphosphate on Raw and Modified Bentonites - Yönten, Vahap; Kubilay, Senol (Asian Journal of Chemistry, 2012)
This study aims to investigate the adsorption of the 2,2-dichlorovinylphosphate (DDVP) on raw and modified bentonite via high pressure liquid chromatography and infrared spectroscopy. The modified bentonites were prepared by adding HNO3 and Na2CO3. The Freundlich adsorption isotherm defines 2,2-dichlorovinylphosphate adsorption in aqueous and aqueous ethanol solutions through raw and modified bentonite. Variables such as temperature, time and pH were observed on 2,2-dichlorovinylphosphate adsorption. Then the capacity for maximum 2,2-dichlorovinylphosphate adsorption was measured on modified bentonite with HNO3 under the conditions of pH 3 and 40 ºC. The modified bentonite with Na2CO3 clay used in experimental work played a major role on the adsorption of 2,2-dichlorovinylphosphate; thus modified bentonite with Na2CO3 is considered to possess better characteristics than modified bentonite with HNO3 and raw bentonite. The Freundlich isotherms of modified bentonite with Na2CO3 in aqueous-ethanol solution were found to be better than isotherms of aqueous solution for a much better 2,2-dichlorovinylphosphate adsorption.